2017
DOI: 10.1681/asn.2016090957
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Ezetimibe Added to Simvastatin in Reduced Kidney Function

Abstract: Efficacy of statin-based therapies in reducing cardiovascular mortality in individuals with CKD seems to diminish as eGFR declines. The strongest evidence supporting the cardiovascular benefit of statins in individuals with CKD was shown with ezetimibe plus simvastatin versus placebo. However, whether combination therapy or statin alone resulted in cardiovascular benefit is uncertain. Therefore, we estimated GFR in 18,015 individuals from the IMPROVE-IT (ezetimibe plus simvastatin versus simvastatin alone in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Based on this strong results from this trial, 2013 ACC/AHA guidelines endorsed the use of ezetimibe patients with eGFR <60 ml/min [ 24 ]. Data from the IMPROVE-IT study mirrored similar findings [ 25 ]. Out of a total 18,144 patients, 3791 had eGFR <60 ml/min.…”
Section: Imrove-it: the Game Changersupporting
confidence: 65%
“…Based on this strong results from this trial, 2013 ACC/AHA guidelines endorsed the use of ezetimibe patients with eGFR <60 ml/min [ 24 ]. Data from the IMPROVE-IT study mirrored similar findings [ 25 ]. Out of a total 18,144 patients, 3791 had eGFR <60 ml/min.…”
Section: Imrove-it: the Game Changersupporting
confidence: 65%
“…According to the most recent guideline for lipid management, 88% of patients who participated in the GCKD study would fulfil criteria for statin prescription [28]. Recent studies also suggested an additional benefit of dual treatment with ezetimibe with decreasing GFR [26, 29]. Implementation of this evidence would further increase medication load and polypharmacy prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…17 In a post-hoc analysis of the randomized trial IMPROVE-IT, comparing participants randomized to simvastatin and ezetimibe versus simvastatin alone, the hazard ratios for the primary endpoint of cardiovascular death, major coronary event, or nonfatal stroke were 0.88 (95% CI: 0.82, 0.95) and 0.87 (95% CI: 0.78, 0.98) at eGFR levels of 60 and 45 mL/min/1.73 m 2 , respectively. 18 In the Further Cardiovascular Outcomes Research with PCSK9 Inhibition in Subjects with Elevated Risk (FOURIER) trial, J o u r n a l P r e -p r o o f participants taking a statin who were randomized to PCSK9i had a lower risk for the primary endpoint of cardiovascular death, MI, stroke, hospitalization for unstable angina, or coronary revascularization compared with their counterparts randomized to placebo (hazard ratio: 0.85; 95% CI: 0.79, 0.92). 19 There was no evidence supporting a difference in the hazard ratios between participants with eGFR ≥90, 60 to 89, and <60 mL/min/1.73 m 2 : 0.82 (95% CI: 0.71, 0.94), 0.85 (95% CI: 0.77, 0.94) and 0.89 (95% CI: 0.76, 1.05), respectively (p-interaction =0.75).…”
Section: Discussionmentioning
confidence: 99%